Inovasi Pangan Fungsional Lokal : Strategi Pasar dan Bisnis Berkelanjutan (Studi Kasus Universitas Sultan Ageng Tirtayasa) - Widia; Amaliah , Lili; Masrikhiyah, Rifatul; Putri Salsabila, Aisya; Candra Mustikaningrum, Ardian; Nafilah, Nafilah; Elvina Rachma, Devi; Putri Wahyuningtyas, Aulia (Politeknik Negeri Bali, 2025)
The economy can be stimulated by functional food entrepreneurship, which involves using local ingredients to create healthful and economically beneficial products through the combination of nutritional knowledge and resources available in the community. The primary objectives of this research are to investigate entrepreneurship prospects by analyzing the desires and opinions of consumers regarding locally produced functional foods, and also to devise sustainable strategies for small and medium-sized businesses. Purchasing decisions are influenced by the level of trust in health claims and the affordability of products. Based on these findings, the study suggests three business strategies: (a) using a local supply chain model to make sure there is a steady supply of raw materials, (b) offering different types of products with varying prices to reach more customers, and (c) helping small businesses improve their ability to research and develop products using scientific evidence.